2020
DOI: 10.3390/su12031215
|View full text |Cite
|
Sign up to set email alerts
|

Tree Ecosystem Services, for Everyone? A Compositional Analysis Approach to Assess the Distribution of Urban Trees as an Indicator of Environmental Justice

Abstract: Trees provide a broad amount of ecosystem services in urban areas. Although it is well documented that trees are essential for the well-being and livability of cities, trees are often not evenly distributed. Studies have found that urban residents with a deprived socioeconomic status are associated with a lower coverage and access to urban trees in their communities, yet a fair distribution of trees contributes to the sustainability and resilience of cities. In this context, the environmental justice movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 68 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Some case studies have assessed this relationship in very different cities. For example, in Boston, Massachusetts [5]; Milwaukee, Wisconsin [2]; Guadalajara, Mexico [8]; and Tampa, Florida [3], and regions such as the Eastern Cape, South Africa [4], different applied studies have revealed the existence of spatial inequalities in the provision of urban trees, which mainly fall on disadvantaged neighbourhoods. However, there are cities where this situation is not appreciated or the data are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case studies have assessed this relationship in very different cities. For example, in Boston, Massachusetts [5]; Milwaukee, Wisconsin [2]; Guadalajara, Mexico [8]; and Tampa, Florida [3], and regions such as the Eastern Cape, South Africa [4], different applied studies have revealed the existence of spatial inequalities in the provision of urban trees, which mainly fall on disadvantaged neighbourhoods. However, there are cities where this situation is not appreciated or the data are not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research has focused on issues such as the accessibility and spatial distribution of green infrastructure, and its relationship with the socio-residential composition of neighbourhoods. As a key part of the urban green infrastructure, the generation of patterns in the spatial distribution of urban trees has been a widely addressed issue in the literature [2][3][4][5][6][7][8]. Urban trees provide several ecosystem benefits, such as temperature regulation [9,10], air-pollution reduction [11], stormwater-runoff control [12] or preserving biodiversity [13], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the application of standard methods to compositional data yielded interpretable and apparently reasonable results, the application of standard methods in compositional data are, at best, inappropriate [26]. As explained by Aitchison [25], Pawlowsky-Glahn and Egozcue [26], Filzmoser, Hron, and Reimann [60], Marcillo-Delgado, Ortego and Pérez-Foguet [80], Cruz-Sandoval, Ortego and Roca [29], the use of standard statistical methods in compositional data originate problems, such as prediction of values outside the sample space, spurious correlations and sub-compositional incoherence, among others.…”
Section: Lessons and Methodological Implicationsmentioning
confidence: 99%
“…Lloyd and co-workers [21] identified problems in the analysis of population studies using standard statistical methods and encouraged the use of log-ratio approach to overcome the different shortcomings of compositional data in population studies. Currently, examples of the application of compositional data methods can be found in a variety of fields, such as in the study of ecosystem services [29], microbiomes [30], tourism [31,32], and business and finance [33], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The species diversity of urban trees is a key component of urban biodiversity [1,2]. High diversity is important for the resilience of urban trees, particularly under changing habitat and environmental conditions [3,4]. High tree diversity is associated with positive emotions and beneficial services, which fulfill important immaterial and non-consumptive human needs [5].…”
Section: Introductionmentioning
confidence: 99%